TINJAUAN EKONOMI POLITIK PENYUSUNAN KEBIJAKAN PERENCANAAN PEMBANGUNAN NAGARI KOTO RANTANG - Asri, Silsila (Ensiklopedia of Journal, 2021)
This research is an analysis of political economy policies regarding the practice of formulating the Nagari Development planning policies. Nagari planning is not just a list of development proposals submitted to the local government, more than that, Nagari planning is a political decision taken jointly by the nagari government and the nagari community.RPJM Nagari and RKP Nagari which are further stipulated in a Nagari Regulation are policy making products that involve the Nagari Government as the executive body, Bamus as the legislative body and elements of society. This research uses qualitative analysis using a theoretical framework of Political Economy Analysis. Political economyframework analized the decision making process by indentified the structural characteristic, institusions as the rule of the games, actors and dynamic interaction. The results of document analysis, interviews and observations show that in the formulation of development planning policies the Nagari Koto Rantang Government has institutionally implemented an empowering and participatory policy-making model through nagari deliberations and development planning deliberations in accordance with applicable laws and regulations. However, in practice, the consensus obtained from the deliberations was dominated by the nagari elite consisting of adat representatives, village officials and group representatives. The political configuration that directs the Nagari Koto Rantang deliberations consists of; supra village government (district representatives); elite nagari consisting of Walinagari along with Nagari Apparatus and wali jorong; Supporters of nagari elites (PKK groups, Gapoktan, UMKM); and Ordinary People.